RESPON BEBERAPA VARIETAS PADI GOGO (Oryza sativa L.) YANG DITANAM DI TANAH ULTISOL TERHADAP AMELIORAN - Tabrani, Gunawan; ', Syahputra; ', Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Increasing production of upland rice can be done by knowing the variety of upland rice which the most tolerance and the best ameliorant for ultisol soil. Variety which show the best response can be recommended to be planted on ultisol soil. This research aimed to get response some varieties of upland rice (Oryza sativa L.) which is planted on ultisol soil the giving of ameliorant. This research has been done in research farm in Faculty of Agriculture, University of Riau from December 2014 untill May 2015. This research was done by factorial experiment 3x4 which was arranged using Split Plot Design. First factor are 3 varieties of upland rice as main plot: Inpago 8, Situ Patenggang and Situ Bagendit. Second factor are giving ameliorants: without ameliorant, calsite lime, natural rock phosphate and kirinyuh green manure. Parameters observed are plant heigh, harvesting date, penicle length, productive tillering amount, percentage of grain pithy, 1000 grain weight, dried grain weight, weight dry straw plant, ratio of grain and straw. Result showed the interaction between varieties of upland rice by giving ameliorant just happened harvesting date while plant heigh and penicle length just be effected by variety and dried grain weight effected by ameliorant. The recomendation to get the best variety of upland rice for ultisol soil according the result of the research is using Situ Bagendit variety by kirinyuh green manure as ameliorant.   Keywords: upland rice, ultisol soil, ameliorant